The Determinants of Musharaka Financing in Indonesia - Fathurrahman, Ayif; Devi, Abriani Sita (Universitas Muhammadiyah Yogyakarta, 2021)
The purpose of this study is to determine the determinants of Musharaka Financing in Islamic commercial banks in Indonesia, which was carried out using secondary data or quantitative data from the period of January 2015 to August 2019. The model used to analyze the results of this regression was the Multiple Linear The dependent variable used in the object of this study was musharaka financing, while the independent variables used in this study consisted of inflation, exchange rates (exchange rates), Return on Assets (RoA), and third-party funds. From the results of the multiple linear regression analysis that has been processed, it can be explained that simultaneously the inflation, exchange rates (exchange rates), RoA, and TPF have a significant effect on Musharaka Financing. However, partially the exchange rate (exchange rate), RoA and TPF have a positive and significant effect on Musharaka financing, while inflation has a positive and insignificant effect on musharaka financing at Islamic Commercial Banks in Indonesia